Dampak pembelajaran daring dan luring terhadap pengetahuan peserta didik pada materi sifat perkalian kelas vi - Algamas Yayang Prifagfirli; Siti Istiyati; siti kamsiyati (Didaktika Dwija Indria, 2025)
.This study aims to describe the impact of online and offline learning on students' knowledge of multiplication properties. This research is a descriptive qualitative research. The subjects in this study were students of class VI at SD Negeri 1 Krasak Boyolali. Data collection techniques through observation, interviews, and documentation. Test the validity of the data used in this study is the source triangulation and technique triangulation. The data analysis technique used in this study used the Miles and Huberman analysis model which consisted of data collection, data reduction, data display, and conclusion drawing/verification. The results of the study showed that the implementation of online learning experienced several obstacles which impacted on the decreased competence of students. A decrease in competence can be seen based on students who are confused about the material that has been taught in online learning. Meanwhile, the offline learning process has an impact on student competence which increases compared to competence in online learning. This increase occurred because teachers were able to convey material more effectively and were able to control students' abilities better in offline learning. Based on these data, it can be concluded that online learning causes a decrease in student competence, while the implementation of offline learning has an impact on participant competency or knowledge. increased education. This research can be used as a reference for further research on the same variables.